A new de novo missense mutation in MYH2 expands clinical and genetic findings in hereditary myosin myopathies - D’Amico, A. (Pergamon Press, 2013)
Congenital myopathy related to mutations in myosin MyHC IIa gene (MYH2) is a rare neuromuscular disease. A single dominant missense mutation has been reported so far in a family in which the affected members had congenital joint contractures at birth, external ophthalmoplegia and proximal muscle weakness. Afterward only additional 4 recessive mutations have been identified in 5 patients presenting a mild non-progressive early-onset myopathy associated with ophthalmoparesis. We report a new de novo MYH2 missense mutation in a baby affected by a congenital myopathy characterized by severe dysphagia, respiratory distress at birth and external ophthalmoplegia. We describe clinical, histopathological and muscle imaging findings expanding the clinical and genetic spectrum of MYH2-related myopathy.